Evaluation of seismoturbidite generation in various tectonic settings: Implications for assessing short-term and long-term seismic cycles - Yakupoğlu, Nurettin (Graduate School, 2022)
In subaqueous paleoseismology, sediment-gravity flow deposits are used as a tool for determination of past earthquakes in marine basins. Decade long investigations of various regions provided important indicators on how to use turbidites in paleoseismology. Earthquake-triggered turbidite deposits (seismoturbidites) are mainly distinguished by their textural, physical, sedimentological and geochemical aspects from the classical turbidites are not classified properly. In this study, variable methods are used to accurately determine the stratigraphic nuances of the sub-units of turbidites using a multi-proxy approach. This approach also helped to construct the depositional model of turbidite generation in various tectonic settings. Turbidites are composed of a coarse basal part that results from the turbulent currents which then overlain by laminar current deposits. Head and body of the turbidity currents carry the coarse sediments followed by turbidity tail flows. These slow-moving currents form a suspension cloud that leads the formation of a homogeneous mud. These homogenous cap deposits are named as homogenites. During the deposition of seismoturbidites, the boundary between homogenites and overlying background sediments become ambiguous. Identification of this boundary is crucial in order to establish accurate age-depth models in the service of paleoseismological usage. Therefore, this thesis tested the demarcation of these boundary with different techniques in different sedimentary settings. This thesis project evaluates three different depositional environments and tectonic settings in terms of seismoturbidite generation. Detailed synthesis of multi-proxies allows differentiating depositional differences of turbidite and homogenite units between confined basin, oceanic margins and lacustrine environments. Multi-proxy approach comprises physical, geochemical and dating methods. Grain size analyses, computed tomography, x-ray radiography, gamma density, magnetic susceptibility, magnetic folation and lineation values are used as physical precursers to determine the turbidite-homogenite units and their lower and upper boundaries within the core stratigraphy. Geochemical precursers are total organic carbon analyses, x-ray fluorescence and x-ray diffraction analyses. These methods have been conducted to show climatic-oceaongraphic periods of the core stratigraphy as well as a strong indicator for demarcation of turbidite-homogenite units. Dating of the sediment cores comprise radiocarbon and radionuclide analyses. All dating outcome is computed in age-depth models for each core to produce robust chronostratigraphy by using "clam" script. Turbidite-homogenite units are neglected during the age-depth model construction since they display instantaneous deposits. Kumburgaz basin, as a confined basin, is located along the North Anatolian Fault in Sea of Marmara, is investigated by a giant piston core covering the last 15 kyrs long sedimentary record. Seventy turbidite-homogenite units were identified in this core by their sedimentological, elemental, magnetic parameters to show the difference between occurrence rates and thicknesses over marine and lacustrine phases of the Sea of Marmara. Within the marine phase, two Holocene sapropelic layers have been detected. Variation of turbidite occurrence is 174 yrs, 114 yrs, 287 yrs and 235 yrs in non-sapropelic marine units, upper sapropel, lower sapropel and lacustrine unit respectively. Turbidite homogenite units are distinguished from the core stratigraphy by using magnetic foliation and elemental distributions showing abrupt drop at the boundary between homogenites and overlying background sediments. Moreover, thesis focuses on Çınarcık and Central basins of Sea of Marmara as well in order to show the depositional differences between sedimentary basins. Turbidite occurrence rates compared between three basins varies within the last six kyrs sedimentary record. Within the same period of time occurrence rates are different in each basins since it is related with the sediment input of the basins, their submarine canyon activity and the location of the coring as well. An oceanic margin, Hikurangi trough is located at the east of Northern Island in New Zealand. Four sediment cores were recovered from different locations to test the detrital differentiation and depositional variations. Number of detected turbidites are not constant between the studied cores even though the cores cover the same amount of time. Physical characteristics and extensive geochemical proxies of the sediments reveal the transition between homogenites and overlying hemipelagites. Demarcation is determined by the combination of elemental and mineralogical distribution of sediments. In homogenites, generally detrital plagioclase and K-feldspar is enriched however in hemipelagic sediment organic calcite is the dominant mineral which is supported by high Ca and Sr count levels. Lake Hazar is located along the East Anatolian Fault at in eastern Turkey. Eleven gravity cores were recovered from various parts of the lake providing a great laboratory to evaluate different depositional processes. The 6 kyrs long sedimentary record is correlated with historical earthquake catalogues showing accurate correlation between turbidites and the last 1500 yrs of large earthquake activity. The sedimentary traces of the most recent 2020 Sivrice and 1971 Bingöl earthquakes were recorded as several turbidite units within the lake basin. Because of the dense coverage of gravity cores it was possible to differentiate four depositional facies based on our analysis. Accordingly, massif, graded, laminated and fluctuated turbidites were detected that represent various depositional conditions. Distribution of facies is done by extensive grain size analyses of the sediments. Mean grain size, sorting, skewness formulations and their cluster distributions showed the boundary between turbidite and overlying lacustrine sediments as well as their depositional patterns. Consequently, this thesis discusses the depositional parameters that control the turbidite-homogenite generation by investigating three different sedimentary environments a confined basin, Sea of Marmara, a lacustrine environment, lake Hazar and an oceanic margin, Hikurangi trough. An important conclusion shows that earthquake triggered turbidites, their occurrence rate and turbidite thicknesses differ based on the detrital component of the catchment area, sediment budget, climatic factors and morphological variations. Seismoturbidites are currently the only tool to evaluate earthquake recurrence on submarine fault systems. However, since these deposits are an indirect precursor of earthquake faulting, they need to be discussed carefully when assessing earthquake recurrence of a certain fault system. Seismoturbidites can be a robust tool if; a) a reliable age-depth model can be constructed, b) multiple cores can be recovered strategically location-wise, c) the time period spans max 6 kyrs to avoid the climatic and oceaongraphic effects of turbidite deposition.
Farklı tektonik ortamlarda sismotürbidit oluşumu: Uzun ve kısa deprem döngüleri hakkında çıkarımlar
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: marine geology; deniz jeolojisi; sualtı paleosismolojisi; subaqueous paleoseismology